First trip up the Yukon River by the steamboat VICTORIAN, Yukon Territory, 1899. - Hegg & Co.
Caption on image: "Victorian's first trip up the Yukon in 1899" PH Coll 246.35 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number